The Model Of Local Regulation Of The Human Rights Fulfillment Based On Progressive Law - Neta, Yulia; Budiyono, Budiyono; Firmansyah, Ade Arif (Universitas Negeri Gorontalo, 2021)
One of the materials for the amendment of the 1945 Constitution is the guarantee of human rights and constitutional rights of citizens. This change can be seen as a manifestation of awareness about the importance of protecting the human rights and constitutional rights of citizens, which grows and becomes the spirit of reform. Local governments have an important role in presenting the spirit of reform by presenting Regional Regulations for the Fulfillment of Human Rights. The material model for the content of the Local regulation Fulfillment of Human Rights based on progressive law relies on three things, namely: laws and regulations that regulate human rights both vertically and horizontally, the contextual reality of the recognition and protection of human rights found in local communities and thirdly for humans and humanity. Systematically, the division of chapters containing the content in it consists of: general provisions; principles and objectives; type of human rights; human rights recognition; protection of human rights; fulfillment of human rights; community participation; guidance and supervision; funding and closing provisions. By using the socio-legal approach, this paper describes the material model for the content of regional regulations regarding the fulfillment of human rights based on progressive law.